Variability of Foveal Avascular Zone Measurements Among Filipino Eyes Using Optical Coherence Tomography Angiography - Roberto Luis F. Franco, MD, DPBO; Carlo Antonino L. Nasol, MD, DPBO, FPCS (Philippine Journal of Ophthalmology, 2025)
Objective: To determine the foveal avascular zone (FAZ) thickness and other FAZ measurements in eyes of healthy Filipino adults aged 20-49 years.